2020
DOI: 10.1002/jcp.29658
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics reveals different pathological processes of adipose tissue, liver, and skeletal muscle under insulin resistance

Abstract: Type 2 diabetes mellitus is the most common type of diabetes, and insulin resistance (IR) is its core pathological mechanism. Proteomics is an ingenious and promising Omics technology that can comprehensively describe the global protein expression profiling of body or specific tissue, and is widely applied to the study of molecular mechanisms of diseases. In this paper, we focused on insulin target organs: adipose tissue, liver, and skeletal muscle, and analyzed the different pathological processes of IR in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 214 publications
(154 reference statements)
0
4
0
Order By: Relevance
“…Specifically, increase in immune- and fibrosis-related proteins in adipose tissue, increase in branched-chain amino acids and mitochondrial proteins in liver, and excessive availability of fatty acids in skeletal muscle have been strongly associated with increased IR. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, increase in immune- and fibrosis-related proteins in adipose tissue, increase in branched-chain amino acids and mitochondrial proteins in liver, and excessive availability of fatty acids in skeletal muscle have been strongly associated with increased IR. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance is a complex phenomenon that can be caused by diverse pathways. Proteomics studies revealed that there are different pathological processes of insulin resistance in skeletal muscle, adipose tissue, and liver (Li et al 2020 ). Men and women have different body composition and physiology of fat and muscle, and the difference may lead to sex differences in the pathophysiology of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that aged skeletal muscle with decreased oxidative capacity led to altered mitochondrial biogenesis, which may be impaired by age-dependent accumulations of point mutations in human mitochondrial (mt) DNA in addition to pro-inflammatory processes [ 14 , 15 ]. Both mitochondrial dysfunction and chronic low-grade inflammation are associated with insulin resistance.…”
Section: Discussionmentioning
confidence: 99%